The Effect of Compensation, Leadership, and Work Discipline on Employee Performance - Tatoya, Ahmat; Latif, Nurdin; Rina, Rina (International Journal of Business, Law, and Education, 2025)
This study aims to analyse the relationship between compensation, leadership, and work discipline on the performance of cooperative employees. The research approach uses quantitative methods with data analysis through the SPSS version 29 programme, using multiple linear regression analysis and hypothesis testing. Tests include partial test (t test) and simultaneous test (F test). The research subjects were employees of Denmadan XIII Cooperative of North Sulawesi, with a total sample of 30 people. The results showed that the variables of compensation, leadership, and work discipline simultaneously affect employee performance. Together, the three independent variables have a significant influence on the performance of employees of the Koperasi Denmadan XIII Merdeka. Partial test results show that compensation variables significantly affect employee performance, while leadership and work discipline variables also partially contribute significantly to employee performance. This study confirms the importance of compensation, leadership, and work discipline in improving the performance of cooperative employees